ANALISIS IMPLEMENTASI PERATURAN BERSAMA TAHUN 2010 TENTANG SINKRONISASI KETATALAKSANAAN SISTEM PERADILAN PIDANA DALAM MEWUJUDKAN PENEGAKAN HUKUM YANG BERKEADILAN BERKAITAN DENGAN KOORDINASI ANTARA PENYIDIK DENGAN JAKSA PENUNTUT UMUM PADA PROSES PRAPEN - Muharam Asih Novi; Jainah Ompu Zainab (KEADILAN PROGRESIF, 2022)
The Archipelago Insight's view states that development in the field of law throughout the archipelago is based on a single legal entity that applies one national law, namely by making and perfecting laws, enhanced by unification and codification, which in the field of Criminal Procedure Code aims to enable the public to live up to their rights and obligations and in order to improve the attitude and mental development of law enforcers in accordance with their respective functions and authorities towards the establishment and stability of law and justice as well as protection of human dignity and order and legal interests. Fundamental changes in the investigation stage have placed investigators and public prosecutors in a coordinating relationship (functional and institutional) in the context of completing the criminal case investigation process as a series of units. One of the goals of this coordinating relationship is to avoid human rights violations in the investigation process. Technically administratively, a prosecutor can only act as a public prosecutor if a warrant for the appointment of a public prosecutor has been issued against him (P 16 A). Technically, he has only acted as a Public Prosecutor since he delegated the case to the court. Thus, the author conducted a research entitled Juridical Analysis of Implementation of Joint Regulations 2010 Concerning Synchronization of Management of the Criminal Justice System in Realizing Just Law Enforcement Regarding Coordination Between Investigators and Public Prosecutors in the Pre-Prosecution Process. The results of this study are known that the factors that can be an obstacle to the implementation of coordination between investigators and public prosecutors at the pre-prosecution stage are the results of investigations that have been declared complete by the public prosecutor, but not followed by the submission of suspects and evidence, the existenceof arrears in criminal cases that have not been completed. resolved and the termination of the investigation or prosecution of criminal cases